Industrial relations; Incomes data services (London, 1991)
Employment policy and practice differ hugely between member states For human resource managers, therefore, the implications of the Single European Market are critical. Managers must rapidly increase their knowledge and competencies if their organizations are to rise to the challenge of Europe. To meet this demand, the IPM has initiated this series of accessible yet comprehensive guides. Based on extensive research, each handbook covers a key human resource issue on a country-by-country basis to facilitate instant comparison. Together, the books form a unique source of practical guidance on all aspects of employment practice throughout the European Community.
Keywords: Industrial relations